Error Analysis of The Spoken English of The First Semester Students of Arabic Education of IAI DDI Polewali Mandar - Nur Afiah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
The preliminary research focused on finding out the types of errors committed by the first semester students of Arabic Education of IAI DDI Polewali Mandar. The source of data was the spoken English of self introduction during the English subject. The aims was to analyze some error committed. The errors found from the data: the use of auxiliaries, tenses, prepositions, pronouns, plurals, error in pronunciation and some difficult words, phrase, sentence of the spoken English in during English subject of the Arabic Education of IAI DDI Polewali Mandar. The result of the research were used to decided students’needs and abilty of English on preparing the teaching material that were given in the first semester of 2010/2020 academic year.